종사상 지위와 가구 균등화 소득이 치과 의료 미충족에 미치는 영향 : 2018 한국의료패널 자료를 활용한 분석 - 이진하; Jin-ha Lee; 오경재; Gyung-jae Oh (Han'guk Ch'iwisaeng Hakhoe chi, 2023)
Objectives: This study used the 2018 Korea Health Panel Survey data to analyze factors affecting employment status and income relating to unmet dental and medical care needs. Additionally it investigated measures to reduce oral health inequality among various socioeconomic classes. Methods: Descriptive statistics for the subjects’ unmet dental and medical care needs were calculated through chi-square test analysis, and multivariate logistic regression analysis was applied to identify factors affecting the unmet dental and medical care needs. The odds ratio and 95% confidence interval were calculated for each level. These data were analyzed using STATA 17.0 SE (64-bit) version, and the statistical significance level was set to p<0.05. Results: As a result of unmet dental and medical care needs according to general characteristics, the lower the education level (p<0.001), the higher the age (p<0.001) and the lower the household equalization income (p<0.024) and the smoker status (p<0.003) were, respectively. Factors that have a statistically significant impact on unmet dental and medical care needs were divorce, separation and bereavement (p<0.001) in individuals than in married persons, and being smokers than non-smokers (p<0.009). The frequency of unmet dental and medical care needs were found to be lower in the cases of a high school graduate than an elementary school graduate (p<0.018), and of higher household equalization income (p<0.001) than the lowest household equalization income, respectively. Conclusions: It was found that various factors such as age, education level, household equalization income, employment status, type of working hours type, and smoking status affect unmet dental and medical care needs.